(untitled) (UNED Research Journal, 2014)
Telemedicine can be an useful option where direct medical attention is not available. We compared a control group of 177 outpatients receiving direct medical attention with 206 telemedicine outpatients in a Costa Rican university. Of these, 85 % were satisfied with and 98 % would accept telemedicine in the future. Our results support the conclusion that telemedicine is a viable method, widely accepted by the staff of the university, which also helps reduce costs, shorten waiting times, relieve saturation in face to face consultation service and allows early detection of risk factors.